KARAKTERISASI GENETIK IKAN KELABAU (Osteochilus kelabau) DARI BERBAGAI LOKASI DI KALIMANTAN BARAT MENGGUNAKAN METODE RAPD (Random Amplified Polymorphism DNA) - Kusmini, Irin Iriana; Gustiano, Rudy; Mulyasari, Mulyasari (BERITA BIOLOGI, 2011)
Kelabau fish (Osteochilus sp.) is an endemic fish to Kalimantan inland waters that is potential to be developed. The aim of this research was to characterize Kelabau fish and to study the data base (genetic character) of kelabau as well as its relationship. The result showed that the highest polymorphism and heterozigosity was on Kelabau Sintang and the lowest was on Kelabau Kapuas Hulu. The closest genetic distance value were between Kelabau Pontianak-Kapuas Hulu (0.5351) and the furthest were between Kelabau Pontianak-Sintang (0.6852).